Solutions Manual for Econometrics - Baltagi, Badi H.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This Second Edition updates the Solutions Manual for Econometrics to match the Fourth Edition of the Econometrics textbook. It corrects typos in the previous edition and adds problems and solutions using latest software versions of Stata and EViews. Special features include empirical examples using EViews and Stata. The book offers rigourous proofs and treatment of difficult econometrics concepts in a simple and clear way, and it provides the reader with both applied and theoretical econometrics problems along with their solutions.
What is Econometrics? -- A Review of Some Basic Statistical Concepts -- Simple Linear Regression -- Multiple Regression Analysis -- Violations of the Classical Assumptions -- Distributed Lags and Dynamic Models -- The General Linear Model: The Basics -- Regression Diagnostics and Specification Tests -- Generalized Least Squares -- Seemingly Unrelated Regressions -- Simultaneous Equations Model -- Pooling Time-Series of Cross-Section Data -- Limited Dependent Variables -- Time-Series Analysis.
Keywords: Economics; Economics -- Statistics; Statistics; Econometrics; Economics/Management Science; Econometrics; Economic Theory; Statistics for Business/Economics/Mathematical Finance/Insurance.; Statistics for Social Science, Behavorial Science, Education, Public Policy, and Law